Pengenalan Teknologi Hidroponik dengan System Wick (Sumbu) bagi Siswa SMA Negeri 2 Kabupaten Rejang Lebong Bengkulu - Syaiful Eddy; Dian Mutiara; Trimin Kartika; Conny Masitoh; Wahyu Wahyu (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
Planting hydroponics is now an alternative as an effort to get around the limitations of the land. Hydroponics can be done with various techniques, one of which is a simple technique that is using the wick system by utilizing a bottle of used mineral water and husk charcoal as a planting medium. To introduce hydroponic technology with a wick system this training was conducted for students of Rejang Lebong 2 High School, by introducing the basic concepts of hydroponics, namely nursery, nutrition preparation, maintenance to harvesting. For seeding, seedlings are sown on Rockwall as a seeding medium. The results of the activity show that students are skilled at carrying out the stages of activities, so it can be concluded that the application of hydroponic farming techniques using the wick system is very good to be developed among high school students, as the application of science, technology, and entrepreneurship to the world of work, as well as the use of used goods, become highly efficient.